L’Afrique dans les manuels scolaires français (1945-1998) - Sophie Lewandowski (Cahiers de la Recherche sur l'Education et les Savoirs)
Following the colonies’ independence, the French school syllabi were not reformed in the sense of greater openness to other civilisations: on the contrary, after a brief attempt at a break-away in the 1960s, they currently present a form of regression whose processes are highly reminiscent of those colonial materials. This is shown in the analysis of 24 schoolbooks in history-and-geography preparing for the Baccalaureat exam and used between 1945 and 1998 and in the syllabi of the same period. Following the colonialist approach based on the concept of a unique civilisation and essentially describing the political and economic fields through a strict hierarchy (more or less “civilised” or “primitive”), a new openness to other civilisations was introduced with the “Braudel syllabus” in 1957. The concept of diversity of civilisations thereafter allows the tackling of the political and economic, as well as social and cultural fields from the perspectives of plurality and specificity. The withdrawal of this syllabus marks the beginning, in schoolbooks, of the era of economism, when the concept of under-development often restricts the analysis to the economic sphere and re-introduces a strict hierarchy with a unique model (more or less economically “developed” or politically “mature”). The article emphasises the discursive and iconographic processes through which educational tools activate some of the norms recognized at their time.